2020
DOI: 10.1186/s12913-020-05157-x
|View full text |Cite
|
Sign up to set email alerts
|

Access to appropriate health care for non-English speaking migrant families with a newborn/young child: a systematic scoping literature review

Abstract: Background: Recently arrived culturally and linguistically diverse migrant mothers in Western Industrialised Nations are less likely to access health care and are more likely to report negative healthcare experiences than more established migrant or non-migrant populations. This is particularly an issue in Australia where nearly half of all Australians were born overseas or have at least one parent born overseas. Methods: A systematic scoping review was conducted to identify a) the main enablers and barriers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Consistent with our findings, mothers have reported doctors consultations to sometimes be rushed and lacking specialist infant advice [ 53 ]. Differences in language and cultural background of health professionals and recipients is also an important consideration for engagement [ 8 , 54 ]. Many mothers in this study felt they were given time for the interaction and were emotionally supported by the bi-cultural CFHNs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with our findings, mothers have reported doctors consultations to sometimes be rushed and lacking specialist infant advice [ 53 ]. Differences in language and cultural background of health professionals and recipients is also an important consideration for engagement [ 8 , 54 ]. Many mothers in this study felt they were given time for the interaction and were emotionally supported by the bi-cultural CFHNs.…”
Section: Discussionmentioning
confidence: 99%
“…We recruited a large sample for this feasibility study and had a high retention rate, indicating positive uptake from participants and greater representation from the target groups. Our qualitative interviews and acceptability analysis were a strength of this study, particularly as acceptability is a significant enabler for child and family health service access among linguistically diverse migrants [ 8 ] and participants’ experiences in early childhood obesity prevention studies are infrequently reported [ 69 ]. The qualitative follow-up interviews conducted allowed us to explore mothers’ program experiences in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent literature review has identified that there are a lack of evaluated interventions to improve health literacy and health care access for migrant families who speak a language other than English, with the majority of the literature focused on identifying enablers and barriers to health care access rather than testing interventions ( Dougherty et al, 2020 ). However, there is a clear need for these types of interventions given that migrant women have been found to experience lower levels of access to health care and poorer birth outcomes ( Almeida et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…One potential avenue to address barriers to accessing health care is through interventions aiming to improve health literacy. Most research has tended to focus on identifying these barriers rather than trialing interventions to overcome these barriers ( Dougherty et al, 2020 ), and as such, this pilot study is an important contribution to the literature and to practice.…”
mentioning
confidence: 99%